Difference in the expression of inflammatory mediators in gingival crevicular fluid in postmenopausal patients with chronic periodontitis with and without menopausal hormone therapy - Santiago Arias-Herrera; Cristina Bascones-Ilundian; Antonio Bascones-Martínez (Elsevier, 2019)
Objective: Hormonal changes experience by women produce significant changes in the periodontium. The aim of this study is to assess whether menopausal hormone therapy, in patients diagnosed with moderate chronic periodontitis and menopause presents a beneficial effect, in terms of clinical and immunological outcomes. Study design: Thirty subjects with moderate chronic periodontitis and menopause were selected and assigned to two groups in accordance to the presence of menopausal hormone therapy. Periodontal clinical parameters, microbiological samples and immunological variables were assessed in both groups. Inter-group differences were evaluated using non-paired Student t-tests and chi square tests. Also, Pearson coefficient correlation was performed to determine the correlation between variables. Results: There were statistically significant differences between groups for clinical attachment level, probing pocket depth, interleukin 1β and interleukin 6. Smoking habit, deeper PPD and higher Il-6 levels in non-menopausal hormone therapy users group, tend to increase the interleukin 1ß GCF levels. These findings were supported by serum estrogen levels. The variables levels were higher in the menopausal hormone therapy users group. Conclusion: Within the limitations of the present study, the hypothesis that menopausal hormone therapy user's women will show better periodontal status and differences in immunological variables respect to those being non-menopausal hormone therapy users was supported. Keywords: Menopause, Estrogen therapy, Interleukin, Periodontal diseases, Chronic periodontitis